The governance structure of Portuguese and Spanish credit cooperatives: differences and similarities - Cabo, Paula (2012)
The literature recognizes that credit cooperatives are the “appropriate technology” for relatively backward economies, but should fade away or disappear altogether as economic development proceeds. However, surprisingly, they are among the fastest growing groups of financial institutions in some advanced economies. Though the credit cooperatives in Portugal and Spain present relatively small market shares, they perform a very important role in the rural economy. Over the last decades, the Iberian credit cooperatives have adopted a process of economic and financial restructuring, through an intensive wave of mergers and the creation of banking networks: Caja Rural Group, in Spain, and Crédito Agrícola Group, in Portugal. Despite that common path, the Iberian reality is still very different. In this paper we describe the historical roots of Portuguese and Spanish cooperative credit, focusing our analysis on the governance structure, especially on the issues arising from the strict application of traditional cooperative rules.